The relationship of spiritual well-being and aging perceptions with depression in Iranian older adults: a cross-sectional study - Pourghayoumi, Marzieh (Mental health, religion & culture, 2023)
The aim of this study was to determine the relationship between spiritual health and aging perception with depression in older adults in Bushehr city, 2019. The present cross-sectional study designed based on the STROBE statement on 430 elderly people. Systematic multi-stage sampling was performed with the informed consent of participants. The mean age of participants was 66.83 ± 7.91 years. The mean scores of spiritual health, physical health and aging perception were obtained 96.75 ± 10.02, 43.07 ± 4.86 and 58.65 ± 6.69, respectively. The results of the interaction between the variables of spiritual health and perception of aging on depression showed a significant relationship between these variables and depression. The results showed that spiritual health and perception of aging have a significant effect on depression. In other words, older adults who were more aware of their aging process and had higher spiritual health reported less depression.